Perbandingan hasil belajar connected mathematics project dengan pembelajaran konvensional pada siswa sma 1Moch. Fauzi, 2Fahmi Abdul Halim, 3Ibnu Toib - Moch. Fauzi; Fahmi Abdul Halim; Ibnu Toib (Universitas PGRI Semarang, 2021)
Background of the research is teaching learning process that usually make students as passive learners. So that, in mathematics teaching and learning process would be apllied syncron model of Connected Mathematics Projects that make student became active learners. The objective of the research is to know whether any differences between students who have taught Connected Mathematics Project with Conventional teaching and learning process on the geometry topics. Subject of the research 70 students of two classes they are X IPA 2 and X IPA 3. This research is quasy experiment, which one class of experimental group uses Connected Mathematics Project and satu one class of control group uses conventional teaching and learning process. The research result from pretest between experimental and control group is there is no differences between pretest score of experimental and control group which Z count with score of Z count < Z table is 0,31 < 1.96. From post-test has been known if ther is any differences between post-test score with analysing it using score of Z table is 2,26 > 1,96, and the result from experimental group is better than control group with score of Z table is 2,26 > 1,645. By reviewing the result above it has been conclude that there is any differences between the result of teaching and learning process using Connected Mathematics Project (CMP) with conventional teaching and learning on geometry topics on X IPA SMA Negeri 02 Tanggul - Jember 2020/2021 academic year. And the result of Connected Mathematics Project (CMP) is better than conventional teaching and learning process on the geometry topics on the X IPA SMA Negeri 02 Tanggul - Jember 2020/2021 academic year.